Interaction of factor H-binding protein of Streptococcus suis with globotriaosylceramide promotes the development of meningitis. Issue 7 (3rd October 2017) - Kong, Decong; Chen, Zhe; Wang, Junping; Lv, Qingyu; Jiang, Hua; Zheng, Yuling; Xu, Maokai; Zhou, Xuyu; Hao, Huaijie; Jiang, Yongqiang
ABSTRACT: Streptococcus suis is an important emerging zoonotic agent that causes acute bacterial meningitis in humans with high mortality and morbidity. Our previous work showed that factor H-binding protein (Fhb) contributed to virulence of S. suis, but the role of Fhb in the development of S. suis meningitis remained unclear. In this study, we demonstrated for the first time that Fhb contributed to the traversal of S. suis across the human blood–brain barrier by allelic-exchange mutagenesis, complementation and specific antibody blocking studies. We also showed that globotriaosylceramide (Gb3), the receptor of Fhb, was involved in this process and affected S. suis infection-induced activation of myosin light chain 2 through Rho/ROCK signaling in hCMEC/D3 cells. Using a murine model of S. suis meningitis, we further demonstrated that Gb3-deficiency prevented the mice from developing severe brain inflammation or injury. Our results demonstrate that the Fhb-Gb3 interaction plays an important role in the development of S. suis meningitis and might be a potential therapeutic target against S. suis infection.